О некоторых трудностях перевода норвежских модальных глаголов на русский язык (On Some Difficulties in Translating Norwegian Modal Verbs to Russian) - Komarova, Olga (Poljarnyj vestnik, 2004)
The article deals with the translation of Norwegian modal verbs into Rus- sian. The difficulties are often due to different linguistic means of ex- pressing modality in these two languages. While the modal meaning of Norwegian modal verbs is adequately understood and rendered into Rus- sian with the help of modal adverbs, particles and adjectives, some diffi- culty arises in constructing the correct form of the copula verb быть in the Russian translation. The author points out certain aspects of Norwegian modal verb se- mantics and usage, in particular the multiplicity of their modal meanings as stated in Norwegian and Russian dictionaries, and shows that the right way to solve problems of translation into Russian lies in the analysis of both the grammatical and semantic structure of the Norwegian sentence. Mistakes can occur in taking one type of subordinate clause for another (e.g. condition vs. reason) or in neglecting specific cases of usage when the modal verb is used in certain types of clauses with a purely structural function, and as such is not translated into Russian. The article provides a potential learner of Russian with some practi- cal hints on the best way of translating the verbs skulle, ville and kunne in some specific contexts.